The Effect of Risk Management, Intellectual Capital Disclosure, and Leverage on Firm Value - Devian, Claudia; Ekadjaja, Agustin (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study aims to examine the effect of enterprise risk management disclosure, intellectual capital disclosure, and leverage on firm value in food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Methodology/Approach: The research applies a quantitative descriptive method using secondary data from annual and sustainability reports of food and beverage companies listed on the Indonesia Stock Exchange from 2019–2023. Samples were selected through purposive sampling, and data were analyzed using Microsoft Excel and SPSS 25. Results/Findings: The regression model passed the classical assumption tests: normality (sig. 0.077 > 0.05), no multicollinearity (tolerance > 0.10), and no heteroscedasticity (sig. > 0.05). Although initial results indicated positive autocorrelation (DW = 0.925), the Cochrane-Orcutt method resolved this issue. The Adjusted R² value is 0.160, indicating that 16% of firm value variation is explained by the three independent variables. The F-test confirms the model’s overall significance (p = 0.000). Individually, risk management disclosure (X1) shows a significant positive effect on firm value (p = 0.000), while intellectual capital disclosure (X2) and leverage (X3) have negative but insignificant effects (p = 0.225 and 0.070). Conclusions: Risk management disclosure significantly enhances firm value, whereas intellectual capital disclosure and leverage do not show a meaningful impact. Thus, disclosure of risk management plays a vital role in determining firm value in IDX-listed food and beverage companies. Limitations: The scope is limited to food and beverage sub-sector firms listed on the IDX during 2019–2023. Contribution: This study contributes to financial management and corporate governance research by highlighting the importance of risk management disclosure. It offers practical insights for companies, regulators, and investors in improving firm value through transparent risk reporting.